2022
DOI: 10.1021/acsomega.1c05992
|View full text |Cite
|
Sign up to set email alerts
|

On the 2H- to 3C-Type Transformation and Growth Mechanism of SiC Nanowires upon Carbothermal Reduction of Rice Straws

Abstract: SiC nanowires (NWs) and nanoparticles (NPs) fabricated by carbothermal reduction of rice straws with/without FeSi catalysts were characterized by transmission electron microscopy to study the catalyst-facilitated vapor–liquid–solid (VLS) growth against the oriented attachment of the crystals, which underwent 2H- to 3C-type transformation. The cotectic melt of the FeSi catalyst in the Fe-Si-C-O system turned out to promote the VLS growth to form straight and occasionally tapered NWs in contrast to the zigzag on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Liu et al 35 found that hexagonal 2H-, 6H-SiC segments embedded in the 3C matrix formed SFs. Similar results were found by Huang et al 64 and Chen et al , 30 but the content of each phase was not given by them quantitatively. According to calculations, the plane spacing of the (0002) plane in 2H-SiC (2.516 Å), and the (0006) plane in 6H-SiC (2.515 Å) were very close to that of the (111) plane in 3C-SiC (2.516 Å).…”
Section: Resultssupporting
confidence: 83%
“…Liu et al 35 found that hexagonal 2H-, 6H-SiC segments embedded in the 3C matrix formed SFs. Similar results were found by Huang et al 64 and Chen et al , 30 but the content of each phase was not given by them quantitatively. According to calculations, the plane spacing of the (0002) plane in 2H-SiC (2.516 Å), and the (0006) plane in 6H-SiC (2.515 Å) were very close to that of the (111) plane in 3C-SiC (2.516 Å).…”
Section: Resultssupporting
confidence: 83%
“…The formation of solid SiC@SiO 2 NWs occurs via gas–gas reactions between the intermediate gases of SiO and CO (as shown in Table S1). The unavoidable presence of trace amounts of O 2 in the equipment, so in the Si–C–O systems, SiO gas should first be formed through possible solid–solid reactions or solid–gas reactions as follows: , 2 S i false( normals false) + O 2 ( g ) = 2 S i O false( normalg false) normalS normali normalO 2 ( s ) + normalC ( s ) = normalS normali normalO ( g ) + normalC normalO ( g ) normalS normali normalO 2 ( s ) + normalC normalO ( g ) = normalS normali normalO ( g ) + normalC normalO 2 ( g ) normalS normali normalO 2 ...…”
Section: Resultsmentioning
confidence: 99%
“…The formation of solid SiC@SiO 2 NWs occurs via gas–gas reactions between the intermediate gases of SiO and CO (as shown in Table S1). The unavoidable presence of trace amounts of O 2 in the equipment, so in the Si–C–O systems, SiO gas should first be formed through possible solid–solid reactions or solid–gas reactions as follows: , …”
Section: Resultsmentioning
confidence: 99%